2016
DOI: 10.1016/j.micres.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

An autophagy gene, HoATG5 , is involved in sporulation, cell wall integrity and infection of wounded barley leaves

Abstract: The endophytic fungus Harpophora oryzae is a beneficial endosymbiont isolated from wild rice. H. oryzae can not only promote rice growth and biomass accumulation but also protect rice roots from invasion by its close relative Magnaporthe oryzae. Autophagy is a highly evolutionary conserved process from lower to higher eukaryotic organisms, and is involved in the maintenance of normal cell differentiation and development. In this study, we isolated a gene (HoATG5) which encodes an essential protein required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…For the endophytic fungus Harpophora oryzae, the ATG5 gene displays an important role in autophagy, sporulation and cell wall integrity. In the presence of Congo Red the growth is highly inhibited in the atg5 mutants, affecting the mycelial development [72]. Another finding in our investigation was the fact that ATG4 and ATG8 gene disruption resulted in sensitivity to the proteasome inhibitor BTZ.…”
Section: Discussionmentioning
confidence: 51%
“…For the endophytic fungus Harpophora oryzae, the ATG5 gene displays an important role in autophagy, sporulation and cell wall integrity. In the presence of Congo Red the growth is highly inhibited in the atg5 mutants, affecting the mycelial development [72]. Another finding in our investigation was the fact that ATG4 and ATG8 gene disruption resulted in sensitivity to the proteasome inhibitor BTZ.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, deletion of the gene Aolatg4 resulted in an increase in sensitivity to chemical stressors, such as menadione and Congo red (Figure 3). Similarly, deletion of Hoatg5 caused defective in hyphal growth on CM plates containing cell wallperturbing agents, including CFW, SDS, and Congo red, in the endophytic fungus Harpophora oryzae (Liu et al, 2016). Moreover, the vegetative growth of ΔBbatg1 and ΔBbatg8 mutants was inhibited by menadione in B. bassiana (Ying et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yanagisawa and colleagues have analyzed the function of Aoatg1 and detected the Cvt pathway in Aspergillus oryzae 28 . More recently, in the endophytic fungus Harpophora oryzae , it has been shown that autophagy is required for vegetative growth, sporulation and virulence 29 . Selective autophagy may also be significant in pathogenesis, because it has been shown that Atg26-mediated pexophagy is necessary for appressorium-mediated plant infection in the hemi-biotrophic plant pathogenic fungus Colletotrichum orbiculare 16 .…”
Section: Introductionmentioning
confidence: 99%